The relationship between social support, cognitive function and activities of daily living in older people: a cross-sectional study - Feng, Man; Li, Jinxiu; Xie, Fen; Chen, Zhengying (Frontiers in Public Health, 2025)
IntroductionWith the increasing severity of population aging, the prevalence of chronic diseases and disabilities is rising, significantly impacting older people’s activities of daily living (ADL), and overall quality of life. Social support plays a crucial role in maintaining their health, as higher levels of support are associated with better quality of life, while inadequate support can negatively affect cognitive function, and ADL. Therefore, this study aimed to investigate the relationship between social support, cognitive function, and activities of daily living (ADL) in older people.MethodsBetween 2022 and 2023, 1,600 older people were selected for the survey using a multi-stage stratified random cluster sampling method. Participants completed a questionnaire regarding demographics, social support, mini-mental state examination, and ADL. Pearson correlation analysis was used to explore the associations among social support, cognitive function, and ADL.ResultsThe results showed that 81.4% of older people had a medium level of social support, 53.1% had cognitive impairment, and 28.3% had impaired ADL. There was a positive correlation between social support and cognitive function (r = 0.168, p < 0.001), a negative correlation between social support and ADL (r = −0.269, p < 0.001); and a negative correlation between cognitive function and ADL (r = −0.142, p < 0.001).ConclusionThe social support of older people was at a medium level, the cognitive function level was low, and the rate of impairment of ADL was high. There was a significant correlation between social support, cognitive function, and ADL.